The Challenges in Accurate Location of Fiber Cable Faults Using Optical Time Domain Reflectometer - Chibuzo Emeruwa; Charles Amadi Kemka; Juliet Nnenna Chidiebere (Archives of Current Research International, 2025)
Accurate fault localization in optical fiber networks is crucial for maintaining high service reliability and reducing operational downtime. Optical Time Domain Reflectometer (OTDR) technology is widely used for fault detection; however, its accuracy is limited by spatial resolution constraints, dead zones, environmental influences, and signal-to-noise ratio (SNR) degradation. This study investigates these challenges through experimental fault localization tests on a 10 km optical fiber link, analyzing the effects of pulse width selection (10 ns to 1 µs), temperature variations (-20°C to 50°C), mechanical strain, and backscatter noise on OTDR performance. Results show that temperature-induced fiber expansion introduces localization errors of up to 150 meters, while low SNR at extended distances (>8 km) causes uncertainty in event identification, leading to potential misclassification of faults. Furthermore, dead zones of up to 200 meters were observed near high-reflection events, significantly reducing fault detection precision. Multiple hardware, signal processing, and environmental compensation strategies are proposed to address these limitations. High-resolution OTDRs with 5 ns pulse widths improve spatial resolution to 0.5 meters, while coherent OTDR (C-OTDR) and Optical Frequency Domain Reflectometry (OFDR) enable submillimeter fault localization. Wavelet-based denoising reduces measurement noise by up to 40%, enhancing event discrimination.